The formation of community leadership on the environment in the Geography career. Experience from the Paraíso Verde project - Ferreiro Vázquez, Iliana; Domínguez Pacheco, Danay; Suárez Sánchez, Yamirka (Revista Minerva, 2022)
The training of community leaders is one of the challenges facing university careers and especially pedagogical ones, since their link with society is governed by the instructive and transformational character that is established for teachers. The particularity of the students of the GEOGRAPHY career is that their social commission considers nature and society in the direction of the pedagogical process. From this general claim, the analysis of the career reveals that the preparation for leadership also shows means to broaden the treatment of the subject. This work includes the evaluations that the author has made in this regard for the career; the requirements to be taken into account and which must be met by the disciplines and subjects are highlighted. In addition, it emphasizes the experience that has been carried out during several courses and that already contributes results to the fundamental objective of contributing to the formation of pedagogues who act as environmental leaders at school and in the community.